The absence of standard modifiable cardiovascular risk factors does not predict better outcomes in patients with acute coronary syndrome. (25th November 2020) - Gonzalez Del Hoyo, M.I; Peiro Ibanez, O.M; Vaquez-Nunez, K; Dominguez Benito, F; Ferrero, M; Romeu, A; Carrasquer, A; Bonet, G; Rodriguez, J; Bardaji, A
Abstract: Introduction: The standard modifiable cardiovascular risk factors (SMuRFs), like diabetes mellitus, hyperlipidemia, hypertension and smoking, are central elements of the well-established European Society of Cardiology SCORE calculator. However, acute coronary syndromes (ACS) in SMuRF-less individuals are not uncommon. Purpose: Our study aimed to describe the population with and without SMuRFs attended for an ACS and study prognostic factors associated with mortality. Methods: We identified 1347 ACS patients without prior history of cardiovascular disease (ACS, cerebrovascular or peripheral artery disease)attended in our university hospital between 2009 and 2012 and examined the proportion of SMuRF-less patients as well as outcomes.The primary outcome was 5-year all-cause death. Results: Overall, the median age was 63 years, 73.4% were male and 52 patients (7%)had no SMuRFs. The most common SMuRF was hypertension (60%), followed by smoking (47%), dyslipidemia (48%) and diabetes mellitus (27%). In patients with and without SMuRFs there were no differences in the proportion of females (27% vs 28%), age (63.7 years [IQR 54–75] vs 62 years [IQR 53–71]), renal failure (4.7% vs 0%, p=0.159), prior heart failure (1.6% vs 1.9%, p=0.590) and pulmonary obstructive disease (11.3% vs 9.6%, p=0.707). SMuRF-less patients had substantially less angina in the previously month (1.9% vs 19.1%, p<0.001), were less treated previously with aspirin (3.9% vs 18.9%, p=0.006), betablockers (5.8% vs 16.6%, p=0.039)and ACEI/ARAII (0% vs 38.1%, p<0.001). Patients with SMuRFs presented significantly more frequently with a NSTEMI (63.1% vs 48.1%) and less frequently with STEMI (32.3% vs 44.2%) or a non-classifiable ACS (2.7% vs 7.7%), compared to those without SMurFS. In patients with and without SMuRFs, there were no significant differences in Killip I class (95.4% vs 98%, p=0.370)and GRACE risk score (105 vs 103, p=0.694). Patients with SMuRFS compared to those without had a higher systolic blood pressure (141 mmHg vs 131 mmHg, p=0, 03) and a lower glomerular filtration rate (81.8 ml/min/m 2 vs 94 ml/min/m 2, p=0.04). There were no differences in those with and without SMuRFs in performance of angiography (83% vs 90%, p=0.160), but SMurF-less patients had lower proportion of multivessel disease (18.6% vs 38.2%, p=0.011), higher tendency to percutaneous angioplasty (70.6% vs 57.8%, p=0.073) or performance of CABG (6.1% vs 1.1%, p=0.028).At 5-year follow up (IQR 3–7), SMuRF-less patients had a lower mortality (11.5% vs 23.4%, p=0.049).On multivariable Cox Regression age, chronic renal failure, glomerular filtration rate and GRACE score were independent predictors of death. Coronary angioplasty was a strong protective risk factor of death.However, being SMuRF-less was not protective against mortality. Conclusion: The absence of SMuRFs was not an independent predictor of mortality. Our study highlights the importance of the often-overlooked subgroup of ACS patients with atherosclerosis not predicted by SMuRFs. Funding Acknowledgement: Type of funding source: None